Strength and ductility of bulk nanostructured aluminum processed by mechanical milling - Aboulkhair, Nesma Tarik Mohamed (AUC Knowledge Fountain, 2012)
Aluminum's many exceptional properties promote it to be as a strong candidate for several applications in the aerospace, automotive, building and packaging industries to name a few. As a result, strengthening Aluminum has been the interest of many researchers over the time. The most commonly followed approaches are alloying and thermal treatments. However, recently, refining the internal structure of materials until reaching the nano-scale range to improve their mechanical properties has been fostered. Specifically speaking, research adopting this approach on various metals has yielded promising results. One of the techniques used to produce nanostructured Aluminum powders, which is the one employed in this research, is mechanical milling. Aluminum powders were mechanically milled using a high-energy ball mill under argon atmosphere for several milling durations up to 12 hours. The effect of the process control agent used during milling was investigated to determine the suitable amount to be used for best achievable mechanical behavior. Both X-ray diffraction patterns and scanning electron micrographs have revealed the establishment of nanostructured Aluminum by mechanical milling. Bulk samples were synthesized by powder metallurgy. The success of the process of powder consolidation was determined by examining the degree of densification through density measurements. The effect of mechanical milling on the bulk samples has been studied by evaluating the tensile and compressive behaviors of the developed material. The material after milling for 12 hours exhibited a tensile strength that is four folds that of the starting powders. But this elevated strength was at the cost of sacrificing the ductility of the material. Nevertheless, under compressive loading the material behaved in a ductile manner in addition to the improved strength. Peaks for secondary phases have been noticed in the X-ray diffraction patterns for the bulk samples after mechanical milling. The types of these phases remain undetermined, although high suspects of oxides and carbides exist, that might have contributed to the material strengthening. Transmission electron micrographs have ascertained achieving a nanocrystalline structure after milling for 12 hours. The poor ductility of the milled Aluminum acts as a barrier that hinders the utility of the material since almost all the applications require an amount of ductility within certain margins for shaping, manufacturing, and so forth. Hence, post-extrusion annealing was conducted on additional samples in an attempt to improve the ductility. This has been proved quite successful, but still the achieved ductility is nowhere near the range that can help commercialize the newly developed material. It was also remarkable that annealing didn't result in sacrificing the acquired strength; on the contrary, the tensile strength of the material was noticed to have increased. Another approach to compromise the strength and ductility of mechanically milled Aluminum was to mix soft as-received Aluminum powders with the Aluminum powders mechanically milled for 12 hours to produce bi-modally structured Aluminum composite. Two mixing techniques were tried out that are turbula mixer and the high-energy ball mill. Using turbula mixer yielded disappointing results by demonstrating a weak bond between the two constituents. Conversely, using the ball mill for mixing allowed a strong bond to form between the constituents leading to enhancing the ductility of mechanically milled Aluminum for 12 hours without depressing the strength beyond the acceptable range.